CORRELATION-REGRESSION ANALYSIS OF THE INFLUENCE OF ENVIRONMENTAL FACTORS ON THE PHYTOMELIORATIVE EFFICIENCY COEFFICIENT OF TECHNOGENIC LANDSCAPES - Mandryk , О.; Tyrlych , В.; Baraban , К. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article presents results of the correlation-regression analysis aimed at identifying relationships between the phytomeliorative efficiency coefficient (PEC) and the physical-chemical parameters of technogenic landscape environments, particularly the influence of heavy metal present in wastewater. The research object is the spoil heap of the "Mezhyrichanska" coal mine of SE "Lvivvuhillia", currently undergoing natural phytoremediation. The study accounted for spatial correspondence between PEC measurement points and sampling locations, ensuring the reliability of the statistical modeling. To identify the key factors influencing vegetation cover formation on degraded areas, the correlation-regression analysis methods were applied. Statistically significant relationships were established between PEC and such parameters as soil acidity, light intensity, air humidity, radiation background, and concentrations of Mn, K, Ca, and Mg in wastewater infiltrating through the spoil heap body. These chemical elements showed the highest values among all those studied within the sample set, justifying their prioritization in statistical evaluation. The constructed multifactorial models allowed for quantitative assessment of the influence strength of each variable. It was found that the calcium content in the wastewater has a considerable effect on vegetation cover development, while increased soil acidity is a factor that significantly reduces the PEC. The analysis of partial elasticity coefficients enabled the identification and clarification of the factor impact hierarchy on vegetation formation. The obtained results contribute to the development of adaptive phytoremediation strategies and the enhancement of ecological safety in degraded landscapes of mining regions. The proposed approach provides scientific justification for prioritizing certain environmental factors and supports the development of effective phytotechnologies for the rehabilitation of areas affected by coal mining.